Henry Glassie duplication project - Glassie, Henry, 1941-; Kazee, Buell, 1900-1976; Plemmons, Ruby Bowman; Reed, Ola Belle, 1916-2002; Smith, Hobart, 1897-1965 (1979)
Collection of field recordings of folk music and concerts, performed on banjo, fiddle, guitar, harmonica, mandolin, dulcimer, and vocals recorded primarily in North Carolina, also in Virginia, West Virginia, New York, Pennsylvania, and Bloomington, Indiana from 1961 to 1972, most from 1961 to 1967 by folklorist Henry Glassie. Collection also includes interviews with musicians, farmers, and others.
Library of Congress duplication project, 1979. Originals on 25 sound tape reels, 7 in. and 1 sound tape reel, 5 in., various speeds.
Performers include Ola Belle Reed, Hobart Smith, N. T. [Nathan Tab] Ward, Ruby Bowman Plemmons, Madison County Ramblers, Pegram and Parham, Quince and Babe, Uncle Jess Jackson, J. E. Cison, Wesley Sharp, Walter Parham, Lee Wallins, Leonard Glenn, Clifford Glenn, Claude Proffitt, Mack Presnell, Vance Goslin, Ollie Ward, Tab Ward, Jesse Wells, Herman Benton, Girvin Family, Elizabeth Stewart, Buell Kazee, and others.
Recorded at various locations including Asheville, Banner Elk, Brevard, Leicester, South Turkey Creek, Sugar Grove, Todd, and Weaverville, North Carolina; Capon Bridge, West Virginia; Saltville, Virginia; Cooperstown, New York; Sullivan County, New York; Lancaster County, Pennsylvania; and Bloomington, Indiana.
Henry Glassie duplication project (AFC 1979/085), Archive of Folk Culture, American Folklife Center, Library of Congress, Washington, D.C.
In English.
Keywords: Folk music -- Appalachian Region; Folk songs, English -- Appalachian Region; Ballads, English -- Appalachian Region; Old-time music -- Appalachian Region; Fiddle tunes -- Appalachian Region; Square dance music -- Appalachian Region; Farmers -- New York (State) -- Interviews; Field recordings -- North Carolina; Field recordings; Ethnography; Interviews; Oral histories; Concerts